Epidemiology of Non-Melanoma Skin Cancer Patients Attending at Hiwa Hospital in Sulaimani City, Iraq - Mohammed Ali, Bushra; Abas Ahmed, Hiwa (Kurdistan Journal of Applied Research, 2018)
Objectives are to identify the frequency of non-melanoma skin cancer cases were registered at Hiwa hospital and to find out the association between cases and controls with their sociodemographic status and risk factors. A case control approach was used, by retrospective chart review of all non-melanoma skin cancer cases presented between 1st of January 2015 till 31st of December 2016 at Sulaimani Hiwa hospital from which 70 cases conducted and 70 controls from Baxshen hospital. Data entered to Microsoft excel, analysed by SPSS V 21. Chi-square test was employed to assess the association between different variables, P value of 0.05 or less considered as statistical significant This study included 70 cases and 70 controls were age and gender matched, most of the cases were in between age 56-70 years old, illiterate 39(55.7%), jobless 26(37.1%), from urban area 45 (64.3%) , married 65 (92.9%). had sufficient income and barely sufficient. About (64%) of cases had squamous cell carcinoma and (36%) had basal cell carcinoma. Most of the cases had family history of skin cancer (11.4%), and 44 (62.9%) of cases had a history of more than 4 hours exposure to sun in a day and 36 (51.4%) of cases were with normal BMI. Most of the cases 32 (45.7%) with type (O) blood group, not smoking cigarette 51 (72.9%) and not drinking alcohol 69 (98.6%). This study showed a statistical significant association between non-melanoma skin cancer with level of education (P value =0.002), family history (P value = 0.02), time of exposure to sun light (P value of < 0.001) and BMI (p value = 0.001). Skin cancer and cancer percentage were in increase pattern especially non-melanoma skin cancer, most of non-melanoma skin cancer cases were squamous cell carcinoma, with a significant association with level of education, income status, time of exposure to sun light, family history and BMI